Influence of Misalignment on Beveloid Gear Tooth Contact and Dynamic Characteristics in Transfer Case Transmission of AWD Vehicle. (7th March 2022) - Bai, Bo; Kuang, Yuhua; Guo, Wenchao; Mao, Shimin
Abstract : Beveloid gears are usually employed to transfer motion of small shaft angle, but the assembly errors or misalignment can affect the gear tooth contact and dynamic performance. A dynamic model and tooth contact analysis model of the intersecting beveloid gear pair are established, the defects of the theoretical tooth surface in the meshing are analyzed, and a microgeometry modification method to improve the meshing performance is proposed. At the same time, the effects of system misalignment and manufacturing errors on its meshing characteristics are considered. By studying the sensitivity of the static and dynamic characteristics of beveloid gear on different misalignment components, the influence laws of misalignment on the contact pattern, transmission error, mesh stiffness, and dynamic excitation force are obtained, which give suggestions for tooth surface modification and support structural stiffness design of beveloid gear with a good NVH performance.